2023
DOI: 10.3847/1538-4357/ac94d8
|View full text |Cite
|
Sign up to set email alerts
|

Cosmicflows-4

Abstract: With Cosmicflows-4, distances are compiled for 55,877 galaxies gathered into 38,065 groups. Eight methodologies are employed, with the largest numbers coming from the correlations between the photometric and kinematic properties of spiral galaxies (TF) and elliptical galaxies (FP). Supernovae that arise from degenerate progenitors (type Ia SNe) are an important overlapping component. Smaller contributions come from distance estimates from the surface brightness fluctuations of elliptical galaxies and the lumin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 147 publications
1
28
0
Order By: Relevance
“…The distance to any galaxy with a (partially) resolved rotation curve may be inferred by fitting it to the calibrated RAR, including marginalisation over the other relevant properties of the galaxy but not necessarily the parameters of the RAR itself. This is analogous to the well-established Tully-Fisher and Fundamental Plane methods, but achieves higher precision (∼10 per cent uncertainty on D rather than 20-25 per cent; Tully et al 2023) at the cost of requiring resolved kinematics. My analysis also supplies enhanced kinematic inclinations, as well as constraints on mass-to-light ratios which may be correlated with other galaxy properties to advance understanding of stellar populations and galaxies' gas content.…”
Section: Discussionmentioning
confidence: 93%
“…The distance to any galaxy with a (partially) resolved rotation curve may be inferred by fitting it to the calibrated RAR, including marginalisation over the other relevant properties of the galaxy but not necessarily the parameters of the RAR itself. This is analogous to the well-established Tully-Fisher and Fundamental Plane methods, but achieves higher precision (∼10 per cent uncertainty on D rather than 20-25 per cent; Tully et al 2023) at the cost of requiring resolved kinematics. My analysis also supplies enhanced kinematic inclinations, as well as constraints on mass-to-light ratios which may be correlated with other galaxy properties to advance understanding of stellar populations and galaxies' gas content.…”
Section: Discussionmentioning
confidence: 93%
“…While the vast majority of galaxies in NED-LVS have redshift measurements, a luminosity distance computed from the Hubble law may not be accurate for the closest galaxies. This is especially true for galaxies at distances less than 40 Mpc (∼3000 km s −1 ) where peculiar velocities are typically a few hundred kilometers per second (Watkins & Feldman 2015;Anand et al 2019;Lilow & Nusser 2021;Tully et al 2023), but can be as high as 1000 km s −1 and a significant fraction of the observed velocity (e.g., Karachentsev et al 2003;Anand et al 2018). For this reason, we choose a final distance based on redshift-independent measurements for the nearest galaxies when available.…”
Section: Final Distancesmentioning
confidence: 99%
“…Large, modern surveys are fundamental for understanding the demographics of galaxies, their distribution in space, and their evolution over cosmic time. Imaging the night sky is an essential first step to acquire coordinates, fluxes, and morphologies needed to identify the galaxies, but mapping the Universe in three dimensions requires distances either by redshift surveys (e.g., Huchra et al 1983) or redshiftindependent distances (e.g., Tully et al 2023). As advances in detectors and computing power have led to an explosion of photometric imaging in different spectral regions and distance measurements, the NASA/IPAC Extragalactic Database (NED) 8 has maintained a comprehensive census of objects beyond the Milky Way (MW) and a fusion of their most fundamental measurements across the electromagnetic (EM) spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called H 0 tension [6,7] has recently overcome the threshold of 5 standard deviations [4,8], essentially ruling out the possibility of a statistical fluke. It is also important to note that several alternative observations of the late-time Universe support the SH0ES result, and none of these measurements suggests a value lower than early Universe estimates [9][10][11][12][13][14][15][16][17][18][19][20][21]. Additionally, Planck-independent observations of the CMB temperature and polarization anisotropies always predict an expansion rate consistent with Planck and never higher than late-time probes [22,23], assuming a ΛCDM scenario.…”
Section: Introductionmentioning
confidence: 99%